1995
DOI: 10.1177/106002809502900611
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone: Review and Assessment of Its Role in the Treatment of Schizophrenia

Abstract: Risperidone is a useful addition to the antipsychotic drug armamentarium, but it should be viewed as an atypical antipsychotic agent. It is reasonable to consider a trial of risperidone in treatment-resistant schizophrenic patients prior to the use of clozapine and as a first-line treatment for newly diagnosed patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…At the start of the study, risperidone had just been introduced on the market. Results from clinical trials indicated a superior effect and a more beneficial side effect profile in comparison with the first‐generation antipsychotics (48–56). However, inclusion criteria for participating in a clinical trial are narrow: a defined age interval, no cardiac or neurological disorders, no abuse, not pregnant or nursing, on safe contraceptives and so on.…”
Section: Discussionmentioning
confidence: 99%
“…At the start of the study, risperidone had just been introduced on the market. Results from clinical trials indicated a superior effect and a more beneficial side effect profile in comparison with the first‐generation antipsychotics (48–56). However, inclusion criteria for participating in a clinical trial are narrow: a defined age interval, no cardiac or neurological disorders, no abuse, not pregnant or nursing, on safe contraceptives and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Risperidone levels are not routinely measured, because therapeutic blood concentrations have not been established (Cardoni 1995). Plasma levels of these drugs, obtained at the time of symptom onset and again with return of the mental status to baseline, could have helped elucidate the mechanism(s) underlying the clinical deterioration.…”
Section: Discussionmentioning
confidence: 98%
“…In comparison to haloperidol, which many consider one of the most effective TAs, risperidone and olanzapine (Ivanov & Charney, 2008;Sikich, Hamer, Bashford, Sheitman, & Lieberman, 2004) as well as clozapine (Kumra et al, 1996) have all demonstrated significantly greater improvements in samples of children and adolescents with schizophrenia. Risperidone, representing probably the most extensively investigated AA, has demonstrated through clinical trials superior efficacy and a more beneficial side-effect profile in comparison with the most prominently used TAs (Ayd, 1995;Cardoni, 1995;Carman, Peuskens, & Vangeneugden, 1995;Fleischacker, 1994;Kane, 1994;Kee, Kern, Marshall, & Green, 1998;Leysen, Janssen, Schotte, Luyten, & Megens, 1993;Marder & Meibach, 1994;Tomasi, de Girolamo, Santone, 2006). Not only do AAs appear to outperform TAs in symptom reduction overall, but symptom improvement tends to also be seen sooner.…”
Section: Schizophreniamentioning
confidence: 93%